Can Rice Farming through the National Strategy Food Estate Increase Regional Production? - Syamsuri Yusup; Yoneta Sonia (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
Food estate is a large-scale food development program that is carried out in an integrated manner. This includes agriculture, plantations and livestock within an area. This research aims to (1) analyze the production factors of lowland rice farming as an effort to increase rice production in the national food estate strategy program in Central Kalimantan; (2) analyze the technical efficiency of lowland rice farming in an effort to increase rice production in the national food estate strategy program in Central Kalimantan. This research was carried out at the Siam Village Food Estate (COE). The sampling method used a random sampling method with a total sample of 89 people. The analysis method uses Cobb-Douglas production function analysis and Frontier Stochastic technical efficiency analysis. Research results: (1) land (X1), seeds (X2), lime (X3), and fertilizer (X4) have a significant effect (α<0.05) on lowland rice production results in the Balanti Siam village food estate, while pesticides (X5), labor (X6), machinery (X7), planting system dummy (D1), and planting pattern dummy (D2) do not have a significant effect on lowland rice production results on food aesthetic land in Balanti Siam village; (2) Farmers in Balanti Siam village are classified as technically efficient with an average technical efficiency of 96.5% (cut-off > 0.70), while individually there are 88 farmers who are classified as technically efficient. The production factors used in rice farming play an important role in production results. By using production factors efficiently, this can increase maximum rice production yields.